Analysis of Psychological Problems of Postpartum Blues: Literature Review - Safaringga, Miranie; Fetrisia, Wiwit; Rahmi, Fani Syinthia; Dahlan, Febry Mutiariami (International Health Sciences Journal, 2023)
Background: The postpartum period is a transitional period associated with many physical and emotional changes for women. The vulnerability to change can lead to problems such as postpartum blues. This condition shows mood changes, crying, sleep disturbances and fatigue, which can be caused by biological, psychological and social and cultural factors. This condition can cause harm to the mother's own health, the health of the baby, and the surrounding environment. Objective: To analyze the psychological problems of postpartum blues. Methodology: the method used in this writing is a literature review study. The databases used in the source search are PubMed, JAMA, Google Scholar, Scimago and Medline. The inclusion criteria for the search for literature sources used were the publication of articles from 2014 to 2023, articles indexed by Scopus or at least Sinta 4 in English, and full articles. The search keywords are postpartum psychological, baby blues, postpartum blues. Literature analysis using PICOT (Population, Intervention, Comparison, Outcome, and Time). Results: The total number of articles used for analysis was 7 out of 20 articles that met the inclusion criteria. Conclusion: susceptibility to change during the transitional period is at risk of causing problems such as postpartum blues. This condition shows mood changes, crying, sleep disturbances, and fatigue. Which can be caused by biological, psychological and social, and cultural factors. This condition can cause harm to the mother's own health, the health of the baby, and the surrounding environment.